The Moderating Impact Of Transformational Leadership On The Influence Of Talent Management And Motivation On Employee Retention - Dewi, Yusi Fadia Kumala; Saptaria, Lina (UNIVED Press, 2026)
This study aims to examine the extent to which transformational leadership can strengthen the relationship between talent management and motivation on employee retention. The research approach used is quantitative with a survey method through the distribution of questionnaires to 120 employees. The data obtained were analyzed using the Structural Equation Modeling–Partial Least Square (SEM-PLS) technique. The results of the study indicate that talent management and motivation have a positive and significant effect on employee retention. In addition, transformational leadership is able to strengthen the influence of talent management on employee retention, but is unable to strengthen the influence of motivation on employee retention. This finding emphasizes the importance of motivation and transformational leadership in improving employee retention. Talent management programs will not be optimal without the support of transformational leadership that can encourage engagement and a sense of belonging in employees. Organizations need to create a work environment that is able to retain high-performing talent through the development of internal motivation and empowering leadership. HR development strategies should be designed in an integrated manner with transformational leadership styles to make retention efforts more effective and sustainable. Other factors such as task clarity, compensation, work culture, work-life balance, and job security may be more relevant in strengthening motivation towards retention decisions.